La justicia indígena en el derecho comparado latinoamericano. - Paguay Estrella, Luis Fernando (2023)
The present research project is entitled "Indigenous justice in Latin American comparative law", the problem that will be investigated has to do with the difficulties between the non-positive competence of indigenous justice and the competence previously established in the Organic Code of the Judicial function for its application. In the last decade of the 20th century there is a similar trend in the constitutional reforms undertaken by the countries that make up the Andean Community of Nations: Colombia, Peru, Bolivia, Ecuador and Venezuela, which makes these processes comparable. These countries have also ratified Convention 169 of the International Labor Organization (ILO) on Indigenous and Tribal Peoples in Independent Countries of 1989, which gives them a similar legal framework. Of these regulatory reforms, the recognition of: a) the multicultural nature of the State/nation/republic, b) the rights of indigenous peoples and peasant communities, c) indigenous law and special jurisdiction stands out. Although these reforms are not exempt from contradictions and limitations, they can be interpreted from a pluralist perspective that allows the foundations of a multicultural State to be built. The objective is to analyze the administration of indigenous justice and the intervention of ordinary justice in Ecuador and other Latin American countries.